Development of a physical literacy consensus statement for Chile: study protocol - Carcamo-Oyarzun, Jaime; Rivera-Gutierrez, Catalina; Henriquez-Alvear, Luis; Delgado-Floody, Pedro; Ferbol Ramirez, Cristina Elizabeth; Díaz Alvarado, Mauricio Andrés; Cumilef-Bustamante, Pablo; Martinez-Lopez, Nicolas; Guarda-Saavedra, Paula; Candia-Cabrera, Paulina; Pavez-Adasme, Gustavo; Castillo-Retamal, Marcelo; et al. (My University, 2025)
Physical literacy is a multidimensional concept that encompasses various aspects of an individual's ability to engage in physical activities throughout their lifespan. As a holistic approach, physical literacy (PL) has generated a lot of interest in the field of physical education, physical activity, and health promotion. Despite its growing popularity, the conceptualization and understanding differ among the countries. In the case of Latin America, the concept of physical literacy is still relatively new and influenced different countries, making complex the contextualization for this region. Considering some aspects of public policies that seek to promote physical activity in Chile, such as the national policy of physical activity and sport or the curricular bases of the subject of physical education, this paper seeks to propose the systematized elaboration based on evidence to generate a contextualized consensus with the different actors that can contribute to the development of physical literacy in Chile. This protocol will involve mixed methods throughout the implementation of six work package processes: (1) review of the existing evidence about physical literacy for its understanding in Spanish-speaking populations, (2) analysis of drawings (preschoolers), semi-structured interviews (children, adolescents, and adults), and focus groups (older adults) to investigate the community's view of physical activity, (3) discussion groups and nationwide online questionnaire to analyze the understanding of the concept of PL by both physical education teachers and political actors, (4) discussion groups to consolidate community perceptions on the relevance of physical activity and physical literacy to prepare a preliminary consensus, (5) national consultation on the draft Physical Literacy Consensus Statement text, and (6) discussion and definition of the Physical Literacy Consensus Statement for Chile. This consensus will help stakeholders, teachers, researchers, and the community in general to understand a common concept of physical literacy, which will allow its development, promotion, and application in the Chilean context. Likewise, this work could be a spearhead to the implementation of physical literacy in Latin America and low-and middle-income countries in other regions. Clinical trial registration The clinical trial will be registered on ClinicalTrials.gov under the name CONALMOT_CL (COnsenso Nacional en ALfabetizaic MOTriz in Spanish: Physical Literacy National Consensus).
Keywords: physical literacy; physical education; physical activity; public policies; consensus